Generation of multi-layered protein bodies in N. benthamiana for the encapsulation of vaccine antigens - Schwestka, Jennifer; Zeh, Lukas; Tschofen, Marc; Schubert, Fabian; Arcalis, Elsa; Esteve-Gasent, Maria; Pedrazzini, Emanuela; Vitale, Alessandro; Stoger, Eva (Frontiers in Plant Science, 2023)
The ability of plants to assemble particulate structures such as virus-like particles and protein storage organelles allows the direct bioencapsulation of recombinant proteins during the manufacturing process, which holds promise for the development of new drug delivery vehicles. Storage organelles found in plants such as protein bodies (PBs) have been successfully used as tools for accumulation and encapsulation of recombinant proteins. The fusion of sequences derived from 27-kDa-γ-zein, a major storage protein of maize, with a protein of interest leads to the incorporation of the chimeric protein into the stable and protected environment inside newly induced PBs. While this procedure has proven successful for several, but not all recombinant proteins, the aim of this study was to refine the technology by using a combination of PB-forming proteins, thereby generating multi-layered protein assemblies in N. benthamiana. We used fluorescent proteins to demonstrate that up to three proteinaceous components can be incorporated into different layers. In addition to 27-kDa-γ-zein, which is essential for PB initiation, 16-kDa-γ-zein was identified as a key element to promote the incorporation of a third zein-component into the core of the protein bodies. We show that a vaccine antigen could be incorporated into the matrix of multi-layered PBs, and the protein microparticles were characterized by confocal and electron microscopy as well as flow cytometry. In future, this approach will enable the generation of designer PBs that serve as drug carriers and integrate multiple components that can be functionalized in different ways.